Generating vague geographic information through data mining of passive web data - Brindley, Paul (2016)
Vagueness is an inherent property of geographic data. This thesis develops a geocomputational method that demonstrates that vague information has the potential to be incorporated within GIS in straightforward manner. This method applies vagueness to the elements of place: types, names and spatial boundaries, generating vague geographic objects by extracting and filtering the differing opinions and perceptions held within web derived data. The aim of the research is threefold: (1) to investigate an approach to automatically generate vague, probabilistic geographical information concerning place by mining differing perspectives from passive web data; (2) to assure the quality of the vague information produced and test the hypothesis that its results are indistinguishable from directly surveying public opinion; and (3) to demonstrate the value of integrating vague information into geospatial applications via examples of its use.